Email filtering using iterated probabilistic weighted K nearest neighbour approach (IPW-k-NN) [electronic resource] - Teh, Hui Pheng, 1985- (2008)
Project Paper (Sarjana Muda Sains (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2008